In vitro Regeneration and Agrobacterium-mediated Transformation of Potato (Solanum tuberosum L.) Cultivars Grown in Mexico (Plant Tissue Culture and Biotechnology, 2013)
Prior to Agrobacterium-mediated genetic transformation in vitro regeneration protocol was established for three potato cultivars (Alfa, Cambray Rosa Morelos and Atlantic) grown in Mexico using leaf, node and internodal explants. Regeneration protocol was developed with or without the intervention of callus. Two potato cultivars, namely, Cambray Rosa Morelos and Alpha were transformed using Agrobacterium tumefaciens strain LBA4404 harboring binary plasmid pBI121 containing the GUS and nptII genes. GUS histochemical assay and PCR analysis were conducted on rooted shoots grown in media without hormones but supplemented with antibiotics. Transformed shoots tested positive through GUS histochemical assay and integration of nptII gene was confirmed by PCR analysis DOI: http://dx.doi.org/10.3329/ptcb.v22i2.14193 Plant Tissue Cult. & Biotech. 22(2): 93-105, 2012 (December)